Exploring pre‐clinical medical students' perception of and participation in active learning: A mixed‐methods transnational study. - Heng, Wendy; Ho, Mei Hui; Mah, Xiu Hui; Lim, Jun Jie; Syamsury, Nabilah Huda Binti Ahmad; Haagensen, Emma; Ong, Edmund Liang Chai; Hubbard, Paul (Medical Education, 2025)
Background: Active learning is a learning process that promotes student engagement in constructing knowledge and conceptual understanding, improves critical thinking skills and develops professional competency. In recent years there has been a significant shift of emphasis in higher education from passive teacher‐centred didactic teaching to active student‐led learning. Although there is abundant literature about active learning, there is a gap in the knowledge of students' perception regarding factors that affect engagement in active learning activities. This project aimed to explore pre‐clinical year medical students' perception of active learning and examine the factors that affect their participation in active learning activities. Methods: A mixed‐method study was conducted with pre‐clinical medical students at Newcastle University Medical School, UK, and Newcastle University Medicine Malaysia. A total of 266 students participated in an online survey questionnaire, with 25 students participating in focus group discussions (FGD). Quantitative data were analysed using descriptive analysis and qualitative data was analysed with thematic analysis. Results: The majority of students (94.7%) recognised that active learning is important for their learning, but had a narrow definition of what active learning constituted, and familiarity with active learning techniques was lacking. Many students' independent learning techniques were centred around methods of 'active recall', with factors affecting the utilisation of active learning techniques mainly focused on time availability, group dynamics in active teaching sessions and teaching styles of educators. Conclusion: Students acknowledged the importance of active learning but are generally unfamiliar with ways to effectively utilise a broad range of active learning strategies. This study demonstrated that it is important for educators to understand firstly how students define active learning as well as how students interact with active learning taught sessions, to ensure that they create an environment where students feel confident to engage in active learning techniques. This study from Newcastle shows medical student understanding of active learning to be focused on recall. The authors recommend a student‐centred, student informed, approach to improving active learning teaching.